Spin-dependent electronic and transport properties of unconventional conductors : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Physics at Massey University, Palmerston North, New Zealand - Ingenhoven, Philip Christopher (Massey University, 2010)
In this thesis we present three different aspects of spin and spin-dependent transport properties in novel materials. Spurred by the prospect of spintronic devices, which use the spin degree of freedom of electrons instead of, or combined with, the charge degree of freedom, we analyse the spin properties of quantum wires, organic conducting polymers and sheets of graphene. First, we examine a quantum wire that is embedded in a two dimensional electron gas. We consider the Rashba spin-orbit coupling, and include the effect of interaction between the conduction electrons. We construct an analytically solvable low-energy theory for the wire, and explore the interaction between two magnetic impurities in the wire. We find that both the spin-orbit coupling and the electron-electron interaction have an effect on the magnetic interaction, and find the magnetic interaction to be tunable by an electric field. Next, we study an organic conducting polymer, which is contacted to magnetised ferromagnetic leads. In semiconducting organic polymers the current is transported by spinful polarons and spinless bipolarons. We simulate the transport through the system, including both types of charge carriers, and find the current to be insensitive to the presence of bipolarons. In addition, we find the bipolaron density to depend on the relative magnetisation of the ferromagnetic contacts. This constitutes an optical way of measuring the spin accumulation in conducting polymers. Finally, we investigate the optical conductivity of graphene. Symmetry arguments indicate the existence of two kinds of spin-orbit coupling in the two dimensional lattice, but there is no consensus about the actual strength of these couplings. We calculated the microwave optical conductivity of graphene including both possible spin-orbit interactions. We find the low frequency dependence of the optical conductivity to have a unique imprint of the spin-orbit couplings. This opens a possibility to experimentally determine both couplings separately.
Keywords: Spintronic devices; Spin and spin-dependent transport properties; Physics; Fields of Research::240000 Physical Sciences